Dynamic calibration of order flow models with generative adversarial networks - Prenzel, F; Cont, R; Cucuringu, M; Kochems, J (Association for Computing Machinery, 2022)
Classical models for order flow dynamics based on point processes, such as Poisson or Hawkes processes, have been studied intensively. Often, several days of limit border book (LOB) data is used to calibrate such models, thereby averaging over different dynamics - such as intraday effects or different trading volumes.